Comparative Study between Degradation Analysis and API 510 Remaining Life Evaluation Method for Feed Gas Filter Vessel Reliability Analysis - Ali, Asad (2012)
The objective of this study is to use the wall thickness data for degradation analysis of feed gas filter vessel and compare the results with remaining life evaluation method provided in API 510. The exponential model for degradation fitted best to the degradation (wall thickness) data. Extrapolation of model gave the failure time for each thickness measurement location, thus providing a failure data set to be analyzed for the reliability function. The results obtained show that the degradation model is more optimistic than API 510 methods and thus it gives a failure free period of 690.33 years which is higher in comparison to life evaluated by using API 510 short term and long term corrosion rates which were calculated to be 510.43 & 628.75 years respectively. These results can be used as a good starting point